Law no. 6 of the years 2013 cancelling law no.5 of the year 2002 promulgated for cancelling the application of the law and system of turning port said city into a free zone and the laws amending thereto = قانون رقم 6 لسنة 2013 بشأن إلغاء القانون رقم 5 لسنة 2002 الصادر بإلغاء العمل بقانون ونظام تحويل مدينة بورسعيد إلى منطقة حرة والقوانين المعدلة له - Egypt; The middle east library for economic services, translator. (2025)
Law no. 6 of the year 2013 cancelling law no. 5 of the year 2002 promulgated for cancelling the application of the law and system of turning port said city into a free zone, and the laws amending thereto قانون رقم 6 لسنة 2013 بشأن إلغاء القانون رقم 5 لسنة 2002 الصادر بإلغاء العمل بقانون ونظام تحويل مدينة بور سعيد الى منطقة حرة والقوانين المعدلة له